2017
DOI: 10.1186/s40317-017-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of salinity during seaward migration of Atlantic salmon post-smolts using acoustic transmitters with data-storage capabilities and conventional acoustic transmitters

Abstract: Background: Development of miniature acoustic transmitters and data-storage tags has provided new insights into ecology of free-ranging aquatic animals. In this study, we used a data-storage-type and a conventional acoustic transmitter, both equipped with a salinity sensor, to measure the in situ salinity experienced by Atlantic salmon postsmolts during the first phase of their marine migration in a Norwegian fjord. The data-storage transmitter conveyed stored salinity data accumulated over a period of up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…1) requirements. This demonstrates the flexibility and capacity provided by contemporary digital electronic fish tags to carry out on-board processing and analysis of sensor signals prior to transmission over the severely bandwidth-limited acoustic channel, a concept that has been utilized successfully in several subsequent telemetry studies [17,[25][26][27]. Even if the recorded sensor data must undergo substantial compression and loss of detail before acoustic transmission, the approach features an advantage over archival tags in that no recapture of the tag is needed to recover the data [25].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…1) requirements. This demonstrates the flexibility and capacity provided by contemporary digital electronic fish tags to carry out on-board processing and analysis of sensor signals prior to transmission over the severely bandwidth-limited acoustic channel, a concept that has been utilized successfully in several subsequent telemetry studies [17,[25][26][27]. Even if the recorded sensor data must undergo substantial compression and loss of detail before acoustic transmission, the approach features an advantage over archival tags in that no recapture of the tag is needed to recover the data [25].…”
Section: Discussionmentioning
confidence: 88%
“…Similar to the findings of Davidsen et al [26], there were no avoidance behaviour in the Atlantic salmon and anadromous brown trout tagged in the study presented here, but in contrast no mortality was recorded which is an advantage of the Al treatment method. In another study, Mitamura et al [27] used a tag based on the design presented here to measure salinity during seaward migration of Atlantic salmon in a fjord in Norway. They utilized both the conventional tracking method and the storage feature of the tag to record the salinity, and found that the statistical data stored on the tag both provided a longer record of data and insight into fish using low salinity areas also in the outer fjord which would be difficult to obtain with a conventional tag and tracking setup.…”
Section: Discussionmentioning
confidence: 99%
“…High salmon lice infestations of wild sea trout Salmo trutta are associated with entry into shallower brackish water or rivers, possibly for self-treatment against lice (Gjelland et al 2014). Once completing their seaward out-migration, wild post-smolt Atlantic salmon also use less saline environments and this may also be a reaction to new salmon lice recruits (Mitamura et al 2017). Despite the potential for Atlantic salmon to self-treat against salmon lice by moving from seawater to freshwater or low salinity environments, this did not occur under the conditions created in FW snorkel cages within the current trial.…”
Section: Effects Of Standard Sw and Fw Snorkel Cages On Salmon Licementioning
confidence: 99%
“…The acoustic receiver thus comprises the inseparable and essential second half of a telemetry system as its performance and placement, together with the transmitter and the channel characteristics, jointly determine the probability of making detections. Although active (mobile) tracking of fish is regularly used and serves as a viable option in many scenarios (Mitamura et al, 2017), the advent of cost-effective automatic monitoring receivers has made it feasible to deploy entire systems of moored receivers (often referred to as passive acoustic telemetry) that enable continuous year-round monitoring of aquatic habitats over a wide span of geographical scopes (Hussey et al, 2015). Such stationary receiver systems are typically organised as clusters of transects (Jackson, 2011;Chaput et al, 2018) or arrays (Simpfendorfer et al, 2002;Hedger et al, 2008;Kraus et al, 2018), or in less regular structures, e.g., focusing on monitoring of specific landmarks or bottlenecks where the fish are expected to dwell or pass (Urke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%